Contribution to the Pteridophyte Flora of Langkawi Archipelago, Peninsular Malaysia - Haja Maideen; Ahmad Damanhuri (Tropical Life Sciences Research, 2015)
The pteridophyte flora of Langkawi Archipelago consists of 130 species, 1 subspecies and 12 varieties in 68 genera and 27 families. This value represents 22.1% of the 647 taxa at the species level and below reported for Peninsular Malaysia. Of the 143 recorded taxa of pteridophytes at the species level and below, 8 species in 2 genera and 2 families are lycophytes and the other 135 taxa in 66 genera and 25 families are monilophytes or ferns. Flora paku pakis di Kepulauan Langkawi mengandungi 130 spesies, 1 subspesies dan 12 varieti dalam 68 genus dan 27 famili. Nilai ini merangkumi 22.1% dari 647 takson di peringkat spesies dan ke bawah yang dilaporkan di Semenanjung Malaysia. Daripada 143 takson paku pakis di peringkat spesies dan ke bawah yang dilaporkan, 8 spesies dalam 2 genus dan 2 famili terdiri dari likofit sementara baki 135 takson dalam 66 genus dan 25 famili terdiri dari monilofit atau paku pakis.